2006
DOI: 10.1089/bfm.2006.1.216
|View full text |Cite
|
Sign up to set email alerts
|

Ankyloglossia in Breastfeeding Infants: The Effect of Frenotomy on Maternal Nipple Pain and Latch

Abstract: Timely frenotomy and breastfeeding counseling is an effective intervention, improving latch and decreasing nipple pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 12 publications
(31 reference statements)
5
90
0
4
Order By: Relevance
“…Forty-six studies reported that they looked for harms; either reporting actual harms or reporting that they found none. These included 5 RCTs, 7-11 1 cohort study, 12 25 case series, 13,15,16,[18][19][20][21][24][25][26][27][28][29][30]32,33,[35][36][37][38][39][40][41][42][43] and 15 case reports. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Most studies reporting harms information explicitly noted that no significant harms were observed (n = 17) 7,[9][10][11]13,15,18,20,24,…”
Section: Harmsmentioning
confidence: 99%
“…Forty-six studies reported that they looked for harms; either reporting actual harms or reporting that they found none. These included 5 RCTs, 7-11 1 cohort study, 12 25 case series, 13,15,16,[18][19][20][21][24][25][26][27][28][29][30]32,33,[35][36][37][38][39][40][41][42][43] and 15 case reports. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Most studies reporting harms information explicitly noted that no significant harms were observed (n = 17) 7,[9][10][11]13,15,18,20,24,…”
Section: Harmsmentioning
confidence: 99%
“…2 The incidence of ankyloglossia is reported to be 1% to 10%, 3 and the association with breastfeeding difficulties is well documented. [3][4][5][6] Symptoms include maternal nipple pain, slow infant weight gain, infant breast refusal, 1 and low maternal milk supply due to poor milk removal. 7 Medical treatment of clinically significant ankyloglossia is frenotomy as recommended by the Academy of Breastfeeding Medicine, 8 and this recommendation has been supported by a recent randomized controlled study by Buryk et al 9 The Hazelbaker Assessment Tool for Lingual Frenulum Function 10 is used to assess ankyloglosssia; however, due to the absence of an accurate definition of ankyloglossia and limited investigation into the condition, no universal guidelines exist to determine when intervention is required.…”
mentioning
confidence: 99%
“…The tongue is completely formed at the end of the second month of intrauterine life (3) , and during its development, lingual brake cells undergo apoptosis and the brake retracts from its apex, forming a fibromucosa fold called the frenulum. There may be, during this stage of programmed cell death, a disturbance and the occurrence of a condition, which is known as ankyloglossia (4) . Ankyloglossia is a congenital anomaly, in which the lingual frenulum is abnormally short and thick (or even thin), and may vary widely in thickness, elasticity and fixation site on the tongue and floor of the mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic pointed to characterize the alteration of the frenulum is related to the functionality of the tongue, which is prevented from protruding beyond the gingival margin, besides the difficulty in touching the incisive papilla, among others (8) . Others consider an alteration when the insertion of the frenulum extends more than usual, towards the apex of the tongue (4) . Still, there is classification of frenulum with the following characteristics: thick, tight or short (9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation